Gliding capacity of different dental flosses - Dörfer, Christof; Wündrich, Dominik; Staehle, Hans Jörg; Pioch, Thomas (Journal of periodontology, 2001)
One of the major concerns with the use of dental floss is the passage of the proximal contact, which might be influenced by the material characteristics of the floss. The aim of this study was to compare the gliding capacities of different flosses with major differences in structure and experimental behavior in vivo.
Gesehen am 12.03.2021